Handling the subjacent complexity of a resocialization program for inmates: A systemic analysis and leverage points - Fernanda Bica de Almeida; Maria Isabel Wolf Motta Morandi; Wislayne Aires Moreira; Shqipe Buzuku; Miguel Afonso Sellitto (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The purpose of this article is to identify the main leverage points that can accelerate the results of the resocialization program via prison work implemented in one of the states of Brazil. The research method was design science research. The main research technique was a systemic analysis, a technique belonging to the field of knowledge of the soft systems methodology. The systemic analysis mapped and listed in closed loops the factors of major influence on the program's results. The sources of information were meetings with specialists from the prison public administration and a survey of the state population. The main deliverable of the study is a systemic map with the identification of two leverage points that, if addressed by the public administration, can remove the main obstacles to the program, the insufficient funds for investment in justice structures, and the skepticism of a large part of the population. The team of public agents responsible for managing the program validated the conclusions.
Keywords: 650; closed-loop systems; complexity; insecurity perception; leverage points; prison working; public security; resocialization; system thinking